2007
DOI: 10.1039/b612233g
|View full text |Cite
|
Sign up to set email alerts
|

2,5-Dimethylphenacyl carbamate: a photoremovable protecting group for amines and amino acids

Abstract: 2,5-Dimethylphenacyl (DMP) carbamates (1a-c) released the corresponding free amines or amino acids in high chemical yields, albeit with quantum yields Phi of only 0.04-0.09, upon irradiation in either aprotic or protic solvents. The photoreaction proceeded principally from the triplet excited state via the E-photoenol. The lifetimes of the triplet enol and the E- and Z-enols in the ground state were determined by laser flash photolysis. The primary photoinitiated transformation liberated a carbamic acid deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…54b Klán and Wirz later demonstrated that 2,5-dimethylphenacyl (DMP) can serve as a PPG for carboxylic acids, 57 phosphates, sulfonates, 54a alcohols (as carbonates), 58 and amines (as carbamates). 59 It was recognized that only moderately good or excellent leaving groups are released efficiently within the photoenol lifetime. Studies by laser flash photolysis showed that photolysis produces the anticipated reaction intermediates, the short-lived triplet enol 3 E , and two longer-lived, ground-state photoenols assigned to the corresponding ( Z ) - and ( E ) - photoenols.…”
Section: Arylcarbonylmethyl Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…54b Klán and Wirz later demonstrated that 2,5-dimethylphenacyl (DMP) can serve as a PPG for carboxylic acids, 57 phosphates, sulfonates, 54a alcohols (as carbonates), 58 and amines (as carbamates). 59 It was recognized that only moderately good or excellent leaving groups are released efficiently within the photoenol lifetime. Studies by laser flash photolysis showed that photolysis produces the anticipated reaction intermediates, the short-lived triplet enol 3 E , and two longer-lived, ground-state photoenols assigned to the corresponding ( Z ) - and ( E ) - photoenols.…”
Section: Arylcarbonylmethyl Groupsmentioning
confidence: 99%
“…60 Only the chloride anion was found to be eliminated from the ( Z ) - xylylenol (τ = 23 μs in methanol) obtained from 2,5-dimethylphenacyl chloride via the singlet pathway. 61 Poor leaving groups such as alcohols and amines that are not efficiently eliminated from the short-lived photoenol intermediates have been attached through a carbonate 58 or carbamate 59 linkage, respectively, which have similar leaving group properties to that of a carboxylate. For example, the galactopyranosyl carbonate 9 releases a carbonate monoester in a high chemical yield that disintegrates thermally into the corresponding alcohol 10 and CO 2 (Scheme 7) 58 on the millisecond time scale.…”
Section: Arylcarbonylmethyl Groupsmentioning
confidence: 99%
“…The obtained spectral curves were processed by a software for overlapping bands decomposition [7,8] and for derivative spectroscopy, developed by us [9]. Laser flash photolysis experiments were performed using a setup that has been described previously [10]. Solutions were placed in quartz cells (4.5 cm long and 1 cm wide) and excited by one of the following excitation sources: a Lambda-Physik EMG 101 excimer laser operating at 308 nm (XeCl) with a pulse energies of ca.…”
Section: Methodsmentioning
confidence: 99%
“…[6,7] Organic carbamates have also played an important role in the area of synthetic organic chemistry, primarily as versatile building blocks or as efficient protecting groups. [8,9] Carbamate syntheses have been accomplished by several methods including carbonization of amines or imines by chloroformate [10,11] or organic acids in the presence of azides [12,13] and organic carbonate under solvent-free conditions, [14,15] and finally by metal-mediated reductive acylation of nitriles [16] or oxime carbonates. [17] In an ongoing work studying the use of 2-oximinoacetoacetate 1 as a building block in the synthesis of pyrrole derivatives as precursors of porphyrin macromolecules, [18,19] we found that when equimolar amounts of oxime 1 and primary aromatic amine 2 were heated in a preheated oil bath at 130 C for 2-3 min, alkyl carbamate 3 was obtained in moderate yield (70-75%) (Scheme 1).…”
Section: Unexpected Reaction Of Oximinoacetoacetate With Amines: a Nomentioning
confidence: 99%